Who Participates : The Supply of Volunteer Labor and the Distribution of Government Programs in Rural Peru - Schady, Norbert R. (World Bank, Washington, DC, 2014)
Numerous analysts have linked volunteering and participation to positive economic and political outcomes. The author uses the 1994 Peru Living Standards Measurement Survey to analyze volunteering patterns in rural Peru. He finds that volunteers in rural Peru have a high opportunity cost of time. They are more educated and more likely to hold a job. Other household characteristics, such as gender, marital status, length of residence, and ethnicity, are also important predictors of the probability of volunteering. Controlling for household characteristics, communities differ widely in aggregate volunteer levels. These differences seem unrelated to differences in patterns of government expenditures. Volunteering may have important benefits in building social capital and encouraging greater ownership of development projects. For example, many public programs in rural Peru and elsewhere ask that the intended beneficiaries "participate" as a means of building trust and social capital, increasing the sustainability of investments and helping self-target investments to the poor. But the author finds that encouraging participation by potential beneficiaries is unlikely to be an effective form of self-targeting, since people with a higher opportunity cost of time volunteer more. Moreover, social programs that require participation may have difficulty reaching some vulnerable groups, such as women and the illiterate.